Nucleotide sequence of an unusual regionally expressed silkmoth chorion RNA: predicted primary and secondary structures of an architectural protein. - Regier, J C (1985)
We have sequenced DNA clones corresponding to the entire coding and 5' untranslated regions and almost all of the 3' untranslated region of a silkmoth chorion RNA which is expressed largely in a subpopulation of follicular epithelial cells (aeropyle crown region). This RNA encodes the E1 protein, one of two components of the prominent "filler" that helps mold the shape of aeropyle crowns. The conceptually translated E1 sequence reveals an alternation in hydrophobic and hydrophilic stretches of amino acids that correlates with certain predictions about its secondary structure. E1 is unusual in revealing no sequence homology with other known chorion sequences and in having an unusually long 3' untranslated region. Sequence analysis of the 5' end of the E1 gene has identified an intron near the end of the signal peptide-encoding region, a feature shared with other chorion genes.